Pharmacognostical Evaluation of Indian Medicinal Plant Altenthera Ficoidea and Polianthes Tuberosa for Anti-Diabetic Activity: A Comprehensive Study on In-Vitro Anti-Diabetic Analysis of Altenthera Ficoidea and Polianthes Tuberosa (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In the given article we had done the in-vitro anti-diabetics analysis of the plant Alternantheraficoidea and Polianthes tuberosa with their phytochemical analysis we had first of all collected the plantand washed it properly with water then after we had washed several times with different solvent after thatwe had taken its ash value and foreign mater then after we had investigated it. Throughout the wholestudy we find the result more satisfying and it is also suggestive for further investigation.